Temporal progression trends of cypress mortality at permanent plots in a National forest reserve of Austrocedrus chilensis (Patagonia, Argentina) - El Mujtar, Veronica Andrea; Andenmatten, Ernesto; Pareja Perdomo, Mariano; Letourneau, Federico Jorge; Grau, Oscar; Gallo, Leonardo Ariel (Instituto Nacional de Investigación y Tecnología Agraria y Alimentaria (España), 2025)
Longevity is a characteristic of forest trees that influences their responses to challenges by biotic and abiotic stresses and the temporal development of symptoms. Monitoring programs have been extensively used to detect the impact of climatic change, air pollution and outbreaks of pathogens on forest health, growth and dynamics. In Argentina, forests of Patagonian cypress are affected since mid twenty century by a mortality process called “mal del ciprés” (cypress mortality), but information about their temporal progression is scarce. In the present work we used a database from a program of dasometric permanent plots to analyse the temporal development of cypress mortality on plot and tree level, and determine qualitatively the spatial distribution of affected trees. Particular pulses of appearance of affected trees shared by all plots, rapid or slow progress of mortality at tree level and a homogeneous distribution of affected trees without a clear pattern of expansion from a central point were determined. The results indicate that the episodic appearance of affected trees can be related with warm and dry climatic periods and suggest that the individuals affected by cypress mortality share some special characteristics such as genetic background, developmental conditions or physiological mechanisms for drought responses.